2022
DOI: 10.34128/jra.v5i1.127
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Narsisme Ceo Dan Arus Kas Bebas Terhadap Kinerja Perusahaan

Abstract: Researchers are actively exploring how CEO narcissism affects CEO behavior in depth. The purpose of this study is to examine the relationship between CEO narcissism and the company's free cash flow to company performance. Quantitative research methods were used in this research with purposive sampling which produced as many as 110 samples from the most index companies in Jakarta Islamic Index from 2017 to 2021. Testing this study using the SPSS 26 application. The results of this study obtained empirical evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
4
1
5
Order By: Relevance
“…Ham et al (2018) contend that CEO narcissism significantly lowers firm performance, which is in contradiction to those studies. It also differs from studies by Kusiyah et al (2022) and Mira et al (2022) which suggest that CEO narcissism does not significantly affect firm performance because all activities carried out by the CEO are not directly related to firm performance, even though the narcissistic personality influences his leadership style and decision-making style. H4: The performance of a firm is positively influenced by CEO narcissism.…”
Section: Ceo Narcissism's Effect On Firm Performancecontrasting
confidence: 82%
See 1 more Smart Citation
“…Ham et al (2018) contend that CEO narcissism significantly lowers firm performance, which is in contradiction to those studies. It also differs from studies by Kusiyah et al (2022) and Mira et al (2022) which suggest that CEO narcissism does not significantly affect firm performance because all activities carried out by the CEO are not directly related to firm performance, even though the narcissistic personality influences his leadership style and decision-making style. H4: The performance of a firm is positively influenced by CEO narcissism.…”
Section: Ceo Narcissism's Effect On Firm Performancecontrasting
confidence: 82%
“…Thus, the narcissistic personality of the CEO can only create a leadership style that produces a different atmosphere in the company and has no effect on the way the CEO utilizes assets to generate profits. A study by Mira et al (2022) and Kusiyah et al (2022) found no relationship between CEO narcissism and firm performance. On the other hand, CEO narcissism has a substantial and positive impact on ROE.…”
Section: Discussionmentioning
confidence: 94%
“…Hasil regresi menunjukkan bahwa kinerja perusahaan (ROA dan Tobin's Q) tidak dipengaruhi oleh CEO narcissism (ukuran foto laporan tahunan dan social media), baik pada periode sebelum pandemi maupun selama pandemi COVID-19. Hasil ini didukung oleh penelitian lain yang menemukan hasil yang sama (Kusiyah et al, 2022;Meilani et al, 2022;dan Muttiarni et al, 2022). Ini dikarenakan narsisme CEO tidak dapat digunakan sebagai alat ukur kinerja perusahaan.…”
Section: Pengaruh Ceo Narcissism Terhadap Kinerja Perusahaanunclassified
“…Pelaporan keuangan tersebut tentu saja berisi informasi-informasi yang berguna dalam membantu pengambilan keputusan bagi para pemakainya(Arnas, Lamtiar, Kurniawati, Kurnianto, & Setiorini, Fidayanti, Kalbuana, & Cakranegara, 2022;Yulistian, Kalbuana, & R., 2020). Pelaporan keuangan adalah seperangkat laporan keuangan dan informasi-informasi lainnya untuk melaporkan keadaan keuangan dari suatu kesatuan usaha (Kusiyah, Kalbuana, & Rusdiyanto, 2022;Pratama, Kalbuana, & Utami, 2020). Seperti ilmu-ilmu lainnya, ilmu akuntansi juga berkembang sesuai dengan perkembangan teknologi dan peradaban kehidupan manusia.…”
Section: Pendahuluanunclassified